The crystal structure of dimethyl 4,4′-[10,20-bis(2,6-difluorophenyl)porphyrin-5,15-diyl]dibenzoate chloroform solvate, C50H32Cl6F4N4O4 - Yang Bingcui; Wang Yuzhou; Cui Hao (Zeitschrift für Kristallographie - New Crystal Structures, 2023)
C50H32Cl6F4N4O4, triclinic, P1‾ $P\overline{1}$ (no. 2), a = 6.6447(6) Å, b = 12.5839(11) Å, c = 14.3335(11) Å, α = 85.845(7)°, β = 85.679(7)°, γ = 85.679(7)°, V = 1188.89(18) Å3, Z = 1, R gt(F) = 0.0605, wR ref(F 2) = 0.1740, T = 200 K.